1989
DOI: 10.1111/j.1440-1681.1989.tb01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Inhibitory Effect of Lead Acetate on Duodenal Contractility in Rat

Abstract: 1. Abdominal colic and constipation are symptoms of lead poisoning in man, but mechanisms of these effects are not yet fully understood. In this study the effect of lead acetate on contractility of rat duodenum was determined in vivo in 70 rats. 2. Rats were orally dosed with 44 mg/kg per day lead as 53 mmol/L lead acetate, for 4 weeks. Motility of the duodenum was recorded with an electrical impedance probe. 3. A significant decrease in the amplitude of contraction waves in case of treated rats was observed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
1
Order By: Relevance
“…Lead can cause abdominal pain through several mechanisms. Lead will negatively affect the motility of intestines [31]. It can be due to the effect of lead on intestinal neural web or on smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Lead can cause abdominal pain through several mechanisms. Lead will negatively affect the motility of intestines [31]. It can be due to the effect of lead on intestinal neural web or on smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the clinical picture may be mistaken for intestinal obstruction or appendicitis [ 60 ]. Mechanistically, it is suggested that lead as well as delta-aminolevulinic acid, the level of which is increased as a consequence of porphyrinopathy in lead poisoning [ 79 ], have negative effects on intestinal motility [ 80 ], the enteric nervous system and smooth muscles [ 79 , 81 ]. Lead interferes with sodium transporter channels of the intestine [ 79 ], but it is also suggested that abdominal pain is due to interaction with calcium in the smooth muscle cells.…”
Section: Discussion Of Casementioning
confidence: 99%
“…Causes for this condition were first summarized by Henry Bockus [ 1 ] but surgeons have described diseases which simulate the acute abdomen already 100 years ago [ 44 ]. Included are among some infectious diseases such as typhoid fever, leptospirosis, malaria or hantavirus infection, a variety of specific clinical states such as possible irritation of the peritoneal pain receptors by osmotic mechanisms or by acid-base disturbance in diabetic ketoacidosis [ 45 ], disturbed capillary and subsequent organ perfusion caused by vascular occlusion in sickle cell crisis [ 46 ], mucosal swelling in angioedema [ 40 , 41 ], autonomic nerve dysfunction in acute intermittent porphyria [ 47 ], a direct oculo-abdominal reflex triggered via the trigeminal nerve and completed via a loop from the nuclei of the vagus nerve by way of the vagal visceral motor and visceral sensory branches in acute glaucoma [ 48 ], negative effects on intestinal motility [ 49 ], the intestinal neural web or smooth muscles caused by lead or increased levels of δ‑aminolevulinic in chronic lead poisoning [ 50 , 51 ], spontaneous bacterial peritonitis and some other conditions listed in Table 1 .…”
Section: Discussion Of Casementioning
confidence: 99%